Review—Lithium-Excess Layered Cathodes for Lithium Rechargeable Batteries. Issue 14 (9th October 2015) - Hong, Jihyun; Gwon, Hyeokjo; Jung, Sung-Kyun; Ku, Kyojin; Kang, Kisuk
Abstract : The exceptionally high gravimetric capacity of lithium-excess layered cathodes (LLCs) has generated interest in their use in lithium-ion batteries (LIBs) for high-capacity applications. Their unique electrochemical and structural properties are responsible for this high capacity, which exceeds the theoretical redox capability of transition metal oxides and have been intensively investigated. However, various fundamental and practical challenges must be overcome before LLCs can be successfully commercialized. The structure of pristine LLCs, which varies with the composition and type of transition metal species used, remains unclear. In addition, the structure continuously changes during electrochemical cycling, which further complicates its understanding. In this review, we discuss the current understanding of LLCs, including their pristine structures, redox chemistries, and structural evolution during cycling, and suggest future research directions to address the critical issues.